Hukum Pidana Dalam Perspektif Qur’ani - Rahmat Sholihin (JOURNAL OF ISLAMIC AND LAW STUDIES, 2021)
Abstract: The implementation of punishments in the Criminal law, according to Islam, is aimed to bring peace among the society fairly and universally. By following the instructions from the Qur'an and Hadith, it can be understood that the implementation of legal punishment is considered effective as a mean to minimize crime.The Qur'an and Hadith has clearly regulated and ordered the criminal acts against the perpetrators of: adultery, accusing adultery (qadzaf), drinking liquor, theft (sariqah), robbery / security disturbance (hirabah), apostasy (riddah), rebellion, murder and persecution. All these crimes are subject to severe legal punishments, such as: qisas, cutting off hands, stoning and the like.Finally, the execution of the perpetrators of the crime, so as to prevent others to do so, also to serve as curative/restorative action for perpetrators who regret of the mistakes they have previously made. Abstrak: Hukum pidana dalam pemberlakuan sanksi menurut Islam adalah bertujuan untuk melindungi ketentraman masyarakat secara universal dan berkeadilan.  Melalui petunjuk Al-Qur’an dan Hadits dapat dimaklumi bahwa pemberlakuan sanksi hukum dianggap efektif sebagai sarana untuk meminimalisir tindak kejahatan. Diantara tindak  pidana yang secara lugas, tegas dan jelas diatur dalam Al-Qur’an dan Hadits yaitu tindak pidana terhadap pelaku:  zina, menuduh zina (qadzaf), meminum minuman keras, pencurian (sariqah), perampokan/pengacau keamanan (hirabah),  murtad (riddah), pemberontakan,  pembunuhan dan penganiayaan. Semua tindak pidana itu mendapatkan sanksi hukum yang cukup berat, seperti: qisas, potong tangan, rajam dan yang seumpamanya.Eksekusi terhadap pelaku tindak kejahatan itu disamping berfungsi sebagai tindakan preventif  bagi orang lain yang ingin mencoba melakukannya, juga berfungsi sebagai tindakan kuratif bagi pelaku yang bertaubat dari kesalahan yang pernah dilakukannya.